Treasure Hunt Educational Game to Improve Grade 1 Early Mathematics Skills: Permainan Edukatif Berburu Harta Karun untuk Meningkatkan Keterampilan Matematika Awal Siswa Kelas 1 - Annisa Salsa Khinanti; Ai Yeni Yuliyanti; Desi Fitriani; Oktaviani Rahma Nurazizah; Naya Fatiyah Kaltsum; Hayindra Narayasa (CV. Media Publikasi Profesional, 2026)
This study aimed to examine whether the educational game stimulus “Mencari Harta Karun” (Treasure Hunt) could improve early mathematics competence among Grade 1 primary pupils. The study was conducted at SDN Puncak (Dusun 1, Desa Genteng) using a quantitative one-group pretest–posttest design. Twenty Grade 1 pupils participated and completed both assessments. The intervention was implemented across six sessions, including preparation of the board-game media and question cards (addition and subtraction within 1–20), a baseline pretest, three guided gameplay sessions facilitated by the class teacher, and a posttest. Primary data were pupils’ pretest and posttest scores, analysed using descriptive statistics and a paired-samples significance test, with effect size reported to estimate practical impact. Results showed an increase in mean scores from 7.85 (SD = 1.56) to 8.95 (SD = 1.28) out of a maximum possible score of 10, suggesting a noticeable improvement in students’ early numeracy achievement and also indicating an average gain of 1.10 points, with a statistically significant difference (p = 0.004). The intervention effect was moderate-to-large (Cohen’s d ≈ 0.74), suggesting educationally meaningful improvement rather than a marginal change. Posttest dispersion was also lower, indicating more consistent attainment across pupils after the intervention. This study contributes evidence that a low-resource, non-digital “Treasure Hunt” game, aligned with indicator-based numeracy assessment, can function as a practical instructional approach for strengthening early mathematics competence in Grade 1. The findings support integrating structured game-based activities into routine early-grade numeracy learning, particularly in contexts with limited access to technology-based learning media.